Assessment of the relation of the optic nerve to the posterior ethmoid and sphenoid sinuses by computed tomography - Hešková, Gabriela; Mellová, Yvetta; Holomáňová, Anna; Výbohová, Desanka; Kunertová, Lenka; Marčeková, Magdaléna; Mello, Milan (Biomedical papers of the Medical Faculty of the University Palacký, Olomouc Czech Republic, 2009)
OBJECTIVE: The aim of this study was to observe the relationship of the sphenoid sinus and posterior ethmoid cells with the optic nerve. MATERIAL AND METHODS: 34 CT scans (68 sides) of paranasal sinuses of patients older than 18 years were retrospectively reviewed. Images were assessed in two planes--axial and coronal. We observed the position and relationship of the optic nerve to the posterior ethmoid and sphenoid sinuses, bony dehiscence and protrusion of the optic nerve into sinuses, and pneumatization of the anterior clinoid process. RESULTS: The most frequent position of optic nerve (ON) was a location close to the posterior ethmoid and sphenoid sinuses without contacting or indentation of the wall--55.9% (38 nerves). The bulging of ON to sphenoid sinus was found in 14.7% (10 nerves) and the course of the nerve through sinus in 16 nerves (23.5%). The position of ON intimately to both sinuses was observed in 5.9% (4 nerves). Protrusion of ON, dehiscence of the bony wall and pneumatization of anterior clinoid process (ACP) was seen in 12 (35.3%), 4 (11.8%) and 9 (26.5%) patients, respectively. Both the protrusion of ON and ACP pneumatization were present in 8 (23.5%) patients on the right side and in 5 (14.7%) patients on the left side. CONCLUSION: Variations of posterior ethmoid and sphenoid sinuses are numerous and may entail potential risk of injury of the ON during sinus surgery. Knowledge of individual differences and configurations in the operation area may help the surgeon to prevent complications. Computed tomography is the preferred radiographic modality for evaluation of bony variations and the pathology of this region.
Keywords: počítačová rentgenová tomografie; Humans; lidé středního věku; Ethmoid Bone; Sphenoid Sinus; Female; Aged; mladý dospělý; dospělí; senioři; lidé; sinus sphenoidalis; Adult; Optic Nerve; ženské pohlaví; Male; Middle Aged; čichová kost; Tomography, X-Ray Computed; Adolescent; nervus opticus; Young Adult; mužské pohlaví; mladiství